Predicting Aberrant Fc-fusion Protein Pharmacokinetics from In Silico Structural Properties and Physiologically Based Pharmacokinetic (PBPK) Modeling - Danilo Tomasoni; Alessio Paris; Roberto Visintainer; Kevin D. Cook; Aochiu Chen; Isabel Figueroa; Veena A. Thomas; Luca Marchetti (The AAPS Journal, 2026)
The fusion of therapeutic proteins to the Fc domain of monoclonal antibodies (mAbs) generally improves the proteins' pharmacokinetic (PK) characteristics, extending in vivo half-lives due to the binding of the Fc domain to the FcRn receptor. Yet, several of these Fc-fusion biologics have been observed to have unexpected rapid clearance associated with non-specific off-target binding. Variability in non-specific clearance is often challenging to predict, not well understood, and ultimately can delay the drug development process. In this investigation, we present a computational approach leveraging in silico protein structural properties to extend a physiologically based pharmacokinetic (PBPK) model of mAbs validated on in vivo plasma PK profiles in mice. Selected model parameters affecting protein half-life have been scaled by analytical functions of a panel of calculated in silico protein properties identified by a novel and ad hoc symbolic regression procedure. The resulting extended model has been successfully validated against an independent set of protein plasma PKs, indicating that it can generalize to novel biologics of the same class. Moreover, the extended PBPK model has a median absolute average fold error (AAFE) of 1.18 (min = 1.09; max = 1.51), where values less than 2 typically indicate a good fit. The results enable the de-risking of aberrant PK behaviors, ultimately leading to the selection of Fc-fusion proteins with increased therapeutic value for patients.

Enhancing aquafaba from lentils and common beans functionality: the role of ultrasound and pH on their microstructure, molecular, and foaming properties - María Eugenia Golzi; Lucas Marchetti; Gabriel Lorenzo (Journal of Food Engineering, 2026)

Ultrafine particles exposure and early subclinical cardiovascular effects from shipping and port activities - Joanna Izabela Lachowicz; Alessandro Murru; Simone Milia; Sergio Pili; Roberta Montisci; Silvia Palomba; Mariusz Jaremko; Maria Francesca Marchetti; Luca Fazzini; Luca Stabile; Giorgio Buonanno; Marcello Campagna; et al. (Science of The Total Environment, 2026)

Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

Long-term forestation-deforestation dynamics in a socioeconomic perspective: The case of Italy, 1936–2018 - Alessia D'Agata; Marco Marchetti; Luca Salvati; Piermaria Corona (Forest Policy and Economics, 2025)

Hybrid meat products: Effects of different pretreated bean flours and levels on the physicochemical and techno-functional characteristics of sausages - Nadia Florencia Nagai; Lucas Marchetti; Gabriel Lorenzo; Silvina Cecilia Andrés (International Journal of Gastronomy and Food Science, 2025)

Applied In-Situ Gamma-Ray Spectrometry for Evaluating Erosion and Fertilizer Accumulation in the Tropical Soil Around Small Isolated Wetland - César Augusto Moreira; José Silvio Govone; Victória Marchetti; Lucas Moreira Furlan; Vania Rosolen (Pure and Applied Geophysics, 2025)

Dietary supplementation with a blend composed of carvacrol, tannic acid derived from Castanea sativa and Glycyrrhiza glabra, and glycerides of medium chain fatty acids for weanling piglets raised in commercial farm - Luca Marchetti; Raffaella Rebucci; Davide Lanzoni; Carlotta Giromini; Lucia Aidos; Alessia Di Giancamillo; Paola Cremonesi; Filippo Biscarini; Bianca Castiglioni; Valentino Bontempo (Veterinary Research Communications, 2024)
This study aimed to evaluate the dietary administration of a blend composed of carvacrol, tannic acid derived from Castanea sativa mill and Glycyrrhiza glabra , medium chain fatty acids (MCFAs) glycerides for weanling piglets. An in vitro digestion followed by total phenolic content (TPC) and total antioxidant activity (TAC) assessment was performed before the in vivo application. At weaning, a total of 210 piglets were randomly allocated to two experimental treatments (7 replicates/15 piglets for each replicate). Control group (CTR) was fed a standard basal diet while the treated group (T) was fed the basal diet mixed with 1.500 mg/kg of blend. After in vitro digestion, TPC and TAC evidenced peaks at the end of oral and gastric phases in comparison to the intestinal one in line with the high content of phenolic compound ( P < 0.05). Treatment conditioned body weight and average daily gain ( P < 0.05), fecal score on 6, 7, and 8 d after weaning ( P < 0.05). At 35d, the T group showed a decrease in salivary cortisol compared to CTR ( P < 0.05). Duodenum and jejunum sections of T piglets revealed higher villi ( P < 0.05), deeper crypts ( P < 0.01), and increased V/C ratio ( P < 0.01). CTR showed a higher expression of duodenal Occludin ( P < 0.05). Jejunal E-cadherin and Occludin were more expressed in T jejunum sections ( P < 0.05). Twelve differentially abundant genera were identified in T group caecal samples. Potentially harmful Clostridium sensu stricto 13 was reduced by the treatment ( P < 0.05). In conclusion, the tested blend positively affected salivary stress markers and the gut health of weaned piglets.

Peabody's legacy: the Moenkopi Formation (Middle Triassic, Anisian) tetrapod ichnofauna—updates from an extensive new tracksite in NE Arizona, USA - H. Klein; S. G. Lucas; J. N. Lallensack; Lorenzo Marchetti (PalZ, 2024)

Active governance of agro-pastoral, forest and protected areas mitigates wildfire impacts in Italy - Gian Luca Spadoni; Jose V. Moris; Giorgio Vacchiano; Mario Elia; Matteo Garbarino; Emanuele Sibona; Antonio Tomao; Anna Barbati; Lorenzo Sallustio; Luca Salvati; Carlotta Ferrara; Saverio Francini; et al. (Science of The Total Environment, 2023)

Introducing digital tools for sustainable food supply management: Tackling food loss and waste in industrial canteens - Ludovica Principato; Stefano Marchetti; Marco Barbanera; Luca Ruini; Leonardo Capoccia; Camilla Comis; Luca Secondi (Journal of Industrial Ecology, 2023)
Reducing food waste is essential if we want to create a more sustainable food system, which is why halving per capita food waste by 2030 has been included in the UN Sustainable Development Goals. The main aim of this paper is to demonstrate that by using digital tools to monitor food provisioning and management within canteens, it is possible to achieve a more sustainable food service management within industrial companies and to reduce the overall quantity and environmental impacts of food preparation and consumption thus achieving economic benefits. Longitudinal 2018 and 2019 data collected from the canteen of a major Italian food production company were analyzed. The results showed that the amount of food lost and wasted has decreased over time, reaping important environmental benefits and illustrating specific differences between the food lost in meal preparation and the food left on employees’ plates. It is therefore important to implement education initiatives and to use digital tools to share food‐related data collected within companies among both employees and kitchen and catering staff in order to raise awareness of their behavioral strengths and weaknesses. From this perspective, new interventions at both kitchen and customer/worker levels are introduced and discussed.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

On the presence of Ichniotherium in the Coconino Sandstone (Cisuralian) of the Grand Canyon and remarks on the occupation of deserts by non-amniote tetrapods - Heitor Francischini; Spencer G. Lucas; Sebastian Voigt; Lorenzo Marchetti; Vincent L. Santucci; Cassandra L. Knight; John R. Wood; Paula Dentzien-Dias; Cesar L. Schultz (PalZ, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Open MICE : an open spatial and temporal data set of small mammals in south‐central Italy based on owl pellet data - Chiara Paniccia; Mirko Di Febbraro; Luca Delucchi; Rocco Oliveto; Marco Marchetti; Anna Loy (Ecology, 2018)
The use of database technologies as a tool for implementing data for quantitative ecological studies and biodiversity conservation planning has recently attracted the attention of the biological community. Despite the fact that the number of biodiversity data sets is quickly rising, online databases of small mammals are still scarce, especially for Mediterranean ecosystems. We implemented the first standardized and accessible georeferenced European database of small mammal occurrences, abundances, and functional traits. Data derived from owl pellets was obtained from different sources, including original field surveys, publications, gray literature, existing databases, and museum collections. The Open MICE database covers the years 1972 to 2017 and includes nearly 50,000 individuals from 23 species (13 Rodentia and 10 Eulipotyphla) at 190 sites in south‐central Italy. Our specific goals in compiling this data set were as follows: (1) to make data that is usually accessible to a restricted audience widely available; (2) to identify the gaps in knowledge about small mammal communities and guide future sampling and conservation efforts; and (3) to gain a first insight into small mammal diversity and abundance in the study area. The potential applications of our spatial relational database are many, from individual‐based to community‐based models as potential indicators of environmental changes at different geographical scales. Given the long‐term support for data storage, the Open MICE database could be further expanded to include other geographical contexts and implemented with new information and traits. We would appreciate that researchers cite this paper if using all or part of the data set. We also request that researchers and teachers inform us of how they are using the data. We intend to keep it up to date as novel studies become available (see Data Availability ).

A Trivalent Enzymatic System for Uricolytic Therapy of HPRT Deficiency and Lesch-Nyhan Disease - Luca Ronda; Marialaura Marchetti; Riccardo Piano; Anastasia Liuzzi; Romina Corsini; Riccardo Percudani; Stefano Bettati (Pharmaceutical Research, 2017)

Transcriptomic profiling of Chamelea gallina from sites along the Abruzzo coast (Italy), subject to periodic localized mortality events - Massimo Milan; Fiorentina Palazzo; Chiara Papetti; Lisa Grotta; Sonia Marchetti; Tomaso Patarnello; Luca Bargelloni; Giuseppe Martino (Marine Biology, 2016)

Reduction of Cadmium Availability to Tobacco (Nicotiana tabacum) Plants using Soil Amendments in Low Cadmium-contaminated Agricultural Soils: A Pot Experiment - Catherine Keller; Monica Marchetti; Luca Rossi; Nicolas Lugon-Moulin (Plant and Soil, 2005)

Restricted indications for the use of antibiotics in acute otitis media - Federico Marchetti; Luca Ronfani; Sergio Conti Nibali; Maurizio Bonati; Giorgio Tamburlini (European Journal of Clinical Pharmacology, 2004)